Neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in hypertensive patients: A prospective cross-sectional study - Sudha S; Birunthavathi M; Mythili M; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2025)
Background: Long-term hypertension progresses to produce atherothrombotic disease. Chronic inflammation may contribute to epithelial dysfunction and atherogenesis and is associated with high blood pressure. Neutrophil-to-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) ratios are the predictors of the cardiovascular diseases. However, studies related to this context are sparse comparatively. Aims and Objectives: The current study explores the NLR and the PLR with hypertension as an indicator of cardiovascular risk. Materials and Methods: The present study is a cross-sectional study conducted at the Department of General Medicine outpatient department, from July 2024 to August 2024. Fifty willing male and female hypertensive patients age group between 40 and 60 years were part of the study. Fifty age and gender-matched normotensive individuals were also included in the study. Blood pressure was measured using a mercury sphygmomanometer. 3 mL of venous blood was collected for complete blood count analysis. Results: There was no significant difference in the demographic parameters among the cases and controls. Pulse rate blood pressure and mean arterial pressure were significantly high in hypertensive patients when compared with the normotensives. Neutrophil count was significantly higher in cases than controls. The NLR was significantly higher in cases than in controls. A positive correlation was observed between the parameters. Conclusion: The present study results support that the NLR and PLR can be used as markers for the diagnosis of cardiovascular diseases. These tests are cost-effective and accurate. Hence, this can be implemented in the diagnosis of cardiovascular diseases. The study recommends further studies involving multiple centers and increased sample size.